Automotive Cyber Security - Karahasanovic, Adi (My University, 2017)
We live in a world that is getting more interconnected by each day and we are witnessing a global change where all the devices in our surroundings are becoming “smart” and connected to the Internet. The automotive industry is also a part of this change. Today’s vehicles have more than 150 small computers (ECUs) inside them creating an in-vehicle network, which controls the vehicle functions similar to the fly-by-wire concept in aviation. These vehicles have multiple connection points to the Internet to offer their users a variety of on-line services. As every device that connects to the Internet gets exposed to various on-line threats, so does the connected vehicle. This is why it is becoming increasingly relevant to address the cyber-security issues in the automotive industry. AUTOSAR is the de-facto standard for the Automotive embedded software today and 80% of global production is based on this standard. This thesis first investigates currently employed security mechanisms in the AUTOSAR after which it shows how the threat modeling process is adapted and adjusted in order to be applied to the connected car and the AUTOSAR standard. The result of this process provided a list of potential security vulnerabilities of the connected car and the AUTOSAR standard. The overall contribution to the automotive industry is achieved by providing two threat modeling processes that are specifically adapted for this domain and can be applied to upcoming releases of the AUTOSAR platform as well as the connected car itself.
Keywords: Informations- och kommunikationsteknik; Data- och informationsvetenskap; Information & Communication Technology; Computer and Information Science